Diabetes self-management by Kenyan adults: Utilising the adapted Kawa River model - Esther Asenahabi Opisa; Marianne Reid (Elsevier, 2024)
The outcome of diabetes management depends on diabetes self-management practices, in which factors assisting or hindering self-care play an essential role. This study identified enablers and barriers to diabetes self-management in adults diagnosed with diabetes in Kenya. The adapted Kawa River model was applied to collect data during semi-structured group discussions (n = 6). Adults (n = 32) diagnosed with diabetes at two geographically distinct county hospitals were purposively selected. The integrated model of behaviour prediction formed the theoretical platform of the study, and data were deductively analysed according to the distal variables in the model. Thematic analysis identified specific categories as enablers and barriers to diabetes self-management. The duplicated categories are economic determinants, dietary factors, support networks, and emotional influences. Health and physical status were identified as additional barriers to diabetes self-management. Findings may be more widely applicable than the context of the presented study. Self-management in diabetes care plays a crucial role, more so due to the worldwide increase in the prevalence of diabetes.